STUDENTS OF PROFESSIONAL TEACHER ON THE JOB EDUCATION PERCEPTIONS FOR E-LEARNING - Yari Dwikurnaningsih (Refleksi Edukatika, 2021)
The purpose of this study is to describe the perception of Teacher Professional Education students towards e-learning. The research method used is the mix method, which is a method that combines quantitative and qualitative research methods. The research was conducted in March 2020, at the Satya Wacana Christian University, Salatiga. The population of this study were 571 students of Satya Wacana Christian University Teacher Professional Education. Determination of the research sample random sampling technique as many as 230 people. Collecting qualitative and quantitative data using closed questionnaires and open questionnaires distributed using google form. The data collection instrument was arranged with 5 choices with a score range of 5 – 1. Quantitative data was analyzed descriptively quantitatively and qualitative data was analyzed using data condensation techniques, data display, and drawing conclusions. The results showed that based on data analyisis, student perception to display aspect, access, interaction, control facility, form and arrangement, and usefulness of e-earning is good. Based on qualitative data, it can be known that the e-learning has quite attractive interface but it still need some addition of pictures or another media; e-learning access is good but it can be a little difficult for people who lived far from the town due to the trouble of internet access; the interaction aspect is good but sometimes it needs a gap to get the feedback from both the lecturer and student; control facility for student who adept with computer is not a problem; the form and structure from e-learning was good, but the learning material still in full text form; learning through online is useful, the weakness is overcomed with face to face in college for material drilling, workshop, and teaching technique.